CIRCULAR DEFECTED GROUND MICROSTRIP BAND-REJECT FILTER DESIGN FOR RADAR COMMUNICATION - Kushwah, Vivek Singh (International Journal of Engineering Technologies and Management Research, 2018)
In this paper, a novel narrow band microstrip band-reject filter is designed using three circular shape defected ground structure (DGS). Three circular shape defected ground structure are linked by a path in the ground plane where etching process is applied. The path length of middle DGS cell is 8 mm and the path length of corner DGS cell is 11 mm whereas the path width of all three DGS cell is 0.6 mm and the radius of circular shape defected ground structure is 2.1 mm. The mid-stop band frequency of the designed filter is 1.61 GHz which is applicable for the satellite and radar communication for the purpose of S-Band. The stop bandwidth of proposed filter is 1 GHz to 2.2 GHz which is useful for narrowband communication. The proposed filter has minimum return loss of 0.11 dB and maximum insertion loss of 60 dB at mid stop-band frequency 1.61 GHz. IE3D 14.1 EM simulation tool is applied for finding out the desired outcome. The proposed microstrip band stop filter has a coverage area of (35.1 mm× 14.4 mm) 505.44 mm2 for the top layer and (16.6 mm× 19 mm) 315.4 mm2 for the ground layer which is more compact as compared to other existing band stop filter designs.